PEMODELAN PERTUMBUHAN EKSPOR INDONESIA 2007-2017 DENGAN PENDEKATAN THRESHOLD VECTOR AUTOREGRESSIVE - Gama Putra Danu (Jurnal Statistika Universitas Muhammadiyah Semarang, 2019)
The declining of export performance in 2011-2017 is due to the weakening position of  the rupiah's per USD and the high inflation rate. Rupiah exchange rate depreciation and inflation have both positive and negative effects on the growth of Indonesian exports. This phenomenon indicates a nonlinear effect of rupiah exchange rate depreciation and inflation on export growth. This study uses TVAR model to capture the nonlinear effects of rupiah exchange rate depreciation and inflation on export growth by making the depreciation of the rupiah exchange rate as a threshold. According to the threshold value, it can be explained that the effect of exchange rate and inflation on export growth can be seen in 2 conditions. The First condition is when the rupiah exchange rate depreciates below Rp 246.2 (rezim 1) and the second condition is when it is above Rp 246.2 (rezim 2). The estimation results show that in rezim 1, export growth (t-1), inflation (t-1) and exchange rate depreciation (t-2) have a negative and significant effect on export growth (t). While in rezim 2, significantly inflation (t-1), exchange rate depreciation (t-2) has a negative effect and inflation (t-2) has a positive effect on export growth (t). Based on these results, government and exporters in making the decision that is related to the export must consider the difference of influence of exchange rate depretiation and inflation to export growth according to the rezim condition